Dinamika Instrumen dan Kelembagaan Pasar Keuangan Syariah: Tantangan dan Prospek Menuju Indonesia sebagai Pusat Keuangan Syariah Global: The Dynamics of Islamic Financial Market Instruments and Institutions: Challenges and Prospects toward Indonesia as a Global Islamic Finance Hub - Azwar Azwar; Bayu Taufiq Possumah (HISAB: Jurnal Akuntansi Lembaga Keuangan Syariah, 2026)
This study aims to describe the Islamic financial instruments in the money and capital markets, analyze the institutional roles in their development, and identify the opportunities, challenges, and prospects of the Islamic financial market in Indonesia. The research employs a library-based qualitative descriptive approach by examining primary and secondary sources such as scholarly literature, DSN-MUI fatwas, and official reports from the Financial Services Authority (OJK), Bank Indonesia (BI), and international institutions. The findings reveal that Islamic financial instruments play a vital role in supporting a halal and just economy, operating under principles free from riba, gharar, and maysir. Institutional frameworks involving OJK, BI, DSN-MUI, IDX, and international bodies such as IFSB and AAOIFI ensure market stability, Sharia compliance, and operational efficiency. Nevertheless, the Islamic financial market faces challenges, including low public literacy, limited regulatory harmonization, and strong competition from conventional and global markets. Despite these constraints, its prospects remain highly promising through integration with the halal industry, strengthened collaboration among stakeholders, and accelerated digital innovation. With appropriate strategies and national policy support, Indonesia holds great potential to emerge as a globally competitive and sustainable Islamic financial hub.